Effect Of Infant Massage On Increasing The Duration And Frequency Of Breastfeeding In Infants Aged 3-6 Months At Al Farid Lubuklinggau Clinic - Sumantri, Eliza; Rusiandy, Rusiandy; Rozi, Veby Fransisca (Journal of International Public Health, 2023)
The problem of low coverage of breast milk in infants is one of the short duration of breastfeeding, efforts to increase the desire of infants to breastfeed by doing baby massage. The research problem is that there are still many infants whose duration and frequency are not long in breastfeeding at the Al Farid Clinic Lubuklinggau. The purpose of the study was to determine the effect of baby massage on the duration and frequency of breastfeeding in infants aged 3-6 months at the Al Farid Clinic Lubuklinggau. The study used a Pre-Experimental research design using One Group Pretest-Postest. The population was 92 people and a sample of 10 people. The types of research data are primary and secondary data. Analysis of breastfeeding duration data using the Paired T-Test test statistic (parametric test) and analysis of breastfeeding frequency using the Wilcoxon test (nonparametric test). The results of the study obtained the average value of breastfeeding duration in infants aged 3-6 months before baby massage was 12.30 and the average value of breastfeeding frequency in infants aged 3-6 months before baby massage was 5.50. The average value of breastfeeding duration in infants aged 3-6 months after baby massage was 17.40 and the average value of breastfeeding frequency in infants aged 3-6 months after baby massage was 7.60. The results of the study obtained the values  value of breastfeeding duration of 0.000, meaning ≤  0.05 and the value  value of breastfeeding frequency of 0.002, so it can be concluded that there is an effect of baby massage on the duration and frequency of breastfeeding in infants aged 3-6 months at the Al Farid Clinic Lubuklinggau. For the Al Farid Clinic Lubuklinggau, in order to be able to routinely implement the SOP for baby massage and to be able to provide counseling and education on breastfeeding duration and frequency to all breastfeeding mothers.